Raising a Modern Ghost: The Magic Lantern and the Persistence of Wonder in the Victorian Education of the Senses - Hunt, Verity (Romanticism and Victorianism on the Net, 2008)
AbstractThis article begins by posing the question of why the eminent Victorian inventor and scientist of optics, Sir David Brewster (1781-1868), chooses to appear in a popular domestic magic lantern handbook of the 1860s, offering a testimonial to the value and importance of that by-that-time familiar parlour toy? By looking back some thirty years or so to Brewster’s Letters On Natural Magic (1832), in which the scientist sets out his project for a popular training of the senses, it highlights the part played by optical entertainments and discourses of magical wonder in Victorian education(s) of the eye, and the particular visuality of wonder as sensory experience. In its discussion of wonder, this article asserts the importance of an emotion frequently excluded from a longstanding picture of a nineteenth century ‘disenchanted’ by science and technology. Someone like Brewster is interesting because he explicitly, programmatically weighs in against irrationality; yet, in explaining away superstitious wonder in terms of, predominantly optical illusion, he retains some of the glamour or fascination of these illusions. As a member of the scientific elite working for the popularisation of optical science and technology for the ‘vulgar’ masses, the scientist may be reassessed and understood as a player in a cultural middle ground, an ambiguous hinterland between positions of outright superstition and outright disillusionment. Exploring the enchantments of technology, this article underlines how optical devices and the visions they offer are instrumental in the evolution of an emerging nexus of Victorian wonders. Through a case study of the magic lantern in nineteenth-century popular science and entertainment, it shows how multiple, diverse ‘wondering’ perspectives gather around a single, longstanding visual machine.